Atezolizumab for children and young adults with previously treated solid tumours, non-Hodgkin lymphoma, and Hodgkin lymphoma (iMATRIX): a multicentre phase 1–2 study. Issue 1 (January 2020) - Geoerger, Birgit; Zwaan, C Michel; Marshall, Lynley V; Michon, Jean; Bourdeaut, Franck; Casanova, Michela; Corradini, Nadège; Rossato, Gianluca; Farid-Kapadia, Mufiza; Shemesh, Colby S; Hutchinson, Katherine E; Donaldson, Francis; et al.
Summary: Background: Atezolizumab is an inhibitor of PD-L1, which can lead to enhanced anticancer T-cell activity. We aimed to evaluate the safety, pharmacokinetics, and activity of atezolizumab in children and young adults with refractory or relapsed solid tumours, with known or expected PD-L1 expression. Methods: iMATRIX was a multicentre, open-label, phase 1–2 trial of patients (aged <30 years) with solid tumours or lymphomas recruited from 28 hospitals in ten countries (USA, France, Italy, UK, Spain, the Netherlands, Denmark, Israel, Switzerland, and Germany). Eligible patients younger than 18 years received 15 mg/kg atezolizumab (maximum 1200 mg); patients aged 18–29 years received the adult dose (1200 mg) until disease progression or loss of clinical benefit. Co-primary endpoints were safety (assessed by incidence of adverse events) and pharmacokinetics (assessed by serum atezolizumab concentrations). Secondary endpoints included the proportion of patients achieving an objective response. This trial is registered with ClinicalTrials.gov, number NCT02541604 . Findings: Between Nov 5, 2015, and April 2, 2018, we screened 115 patients, 25 of whom did not meet the inclusion criteria. 90 patients, with a median age of 14 years (IQR 10–17), were enrolled. At the data cutoff (April 2, 2018), two patients remained on study treatment. 87 (97%) of 90 patients received at least one dose of atezolizumab at 15 mg/kg or 1200 mg and were evaluable for safety. Three patients were not treated owing to either poor clinical condition or withdrawal of consent. In the safety-evaluable population (n=87), the most common adverse events were pyrexia (36 [41%] patients) and fatigue (31 [36%]). The most common grade 3–4 adverse event was anaemia (19 [22%] patients). The most commonly reported serious adverse events were in the categories of infections and infestations; pyrexia was the only serious adverse event reported in more than two patients. 57 (66%) patients had at least one treatment-related adverse event (grade 1–4); fatigue was the most common treatment-related adverse event (17 patients [20%]). There were no fatal adverse events. Mean serum concentrations of atezolizumab were overlapping and comparable between children receiving 15 mg/kg and young adults receiving 1200 mg of atezolizumab every 3 weeks. Serum concentrations of atezolizumab were above the target exposure level in all patients. At 6 months, four patients (5%) achieved an objective response (all partial responses). Interpretation: Although response to atezolizumab was restricted, atezolizumab was well tolerated with generally comparable exposure across populations. Our findings might help to define future development strategies for immune checkpoint inhibitors either by focusing research to specific disease subpopulations that exhibit greater benefit from immune checkpoint inhibitors, or by providing the means to identify therapeutic combination partners that augment T-cell infiltration and proliferation in so-called immune cold tumour microenvironments. Funding: F Hoffmann-La Roche.